Efektivitas Penggunaan Teknik Scaffolding Dalam Meningkatkan Hasil Belajar Matematika Pada Siswa SMP Swasta Al-Washiliyah Medan - FKIP, Edumatica; Sari, Novita; Surya, Edy (Edumatica : Jurnal Pendidikan Matematika, 2017)
This study aims to determine how the effective use of techniques Scaffolding in mathematics and to determine whether through Scaffolding techniques can improve students' mathematics learning outcomes VIII-A.Jenis research is classroom action research with research instruments such as achievement test consisting of initial tests, the test cycle I to cycle II testing and observation to determine involvement of the student and teacher activities. As the subjects in this study were students of class VIII-A which consists of 30 students. The results of the study to the authors present is as follows. In early tests students get completed by 8 students (27%) and do not pass the study there were 22 students (73%) with the average value was 58.8. Results of the tests performed on the first cycle of 30 students there were 20 (67%) students who completed and incomplete there were 10 children (33%) with the average value was 71.6, and the second cycle of the 30 students there are 28 ( 93%) students who completed and 2 (7%) of students did not complete the average value was 85.6. It can be seen that there is an increase of 40% completeness of the initial tests to the first cycle, completeness increase of 26% from the first cycle to the second cycle. From these results it can be concluded that the use of scaffolding techniques to improve learning outcomes in mathematics